Clematis hainanensis (Ranunculaceae), described from Hainan in southern China, is merged with C. leschenaultiana - Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2020)
Based on critical examination of herbarium specimens (including type material), we demonstrate that Clematis hainanensis (Ranunculaceae), described from Hainan in southern China, is not essentially different from C. leschenaultiana, a species widely distributed in China (Chongqing, Fujian, Guangdong, Guangxi, Guizhou, Hainan, Hubei, Hunan, Jiangxi, Sichuan, Taiwan, Yunnan), and also in Indonesia, the Philippines, and Vietnam. We therefore place C. hainanensis in synonymy with C. leschenaultiana herein. Lectotypification is proposed for C. leschenaultiana var. denticulata, which was described also from Hainan and treated as a synonym of C. leschenaultiana. The placement of the name C. splendens is briefly discussed.